Variation In Vitreous Biochemical Constituent Levels With Lengthening Time Since Death And Correlation With Their Blood Levels (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
The Vitreous Humor (VH) is a transparent, gel-like substance that fills the space  between the lens and the retina in the eye. It helps maintain the eye’s shape,  provides support to the retina, and allows light to pass through to the retina where  images are formed. The major function of this fluid is to support the shape of  the eye and transmit light to the retina. In this article, the effect of VH and its  biochemical constituents since the time of death has been analyzed. This research  also demonstrates the changes within biochemical constituents of VH as time  increases after the death of a person. Besides that, this research is significantly  beneficial for future researchers to evaluate changes in levels of VH after death and  correlation with blood levels. Objective: To determine Post Mortem Interval from Potassium (K+) concentration  in Vitreous, correlation of biochemical constituents with both eyes, and an  additional objective is the correlation of levels of Biochemical Constituents i.e.  Na+, K+, Cl-, and Urea in Vitreous and Blood. Material and Method: This study was conducted on the human dead bodies  brought for medico-legal autopsy to the mortuary wing of Department of Forensic  Medicine & Toxicology, Dr. RPGMC, Kangra at Tanda over a length of one year  after obtaining informed consent. “Vitreous Humor” samples were collected  from both eyes, first from the right eye and then from the left eye after external  examination of the dead body at the time of post-mortem examination. Collecting  blood directly from the heart and analyzing ocular fluids can be crucial for  accurate assessments. For instance, VH is often analyzed in forensic investigations
Keywords: Vitreous Humor (VH); Time since death (TSD); Post Mortem Interval (PMI); iochemical constituents